The Correlation between Emotional Intelligence and Social Skills among Islamic Boarding School Students: The Moderating Role of Dormitory Multicultural Environment - Taufik Agung Pranowo; Panggih Wahyu Nugroho; Beta Pujangga Mukti (Cendekia: Kependidikan dan Kemasyarakatan, 2026)
This study investigates the direct effect of emotional intelligence on social skills and the moderating role of the dormitory multicultural environment among Islamic boarding school students. This study employed a quantitative cross-sectional design that involved 600 students aged 13-18 years from 40 pesantren in Central Java and the Special Region of Yogyakarta, selected through multistage cluster random sampling. Data were collected using three adapted and re-validated instruments: the Emotional Intelligence Scale (16 items), the Social Skills Scale (70 items), and the Multicultural Environmental Perception Scale (12 items). Moderated Structural Equation Modeling revealed that emotional intelligence has a significant positive direct effect on social skills (β = 0.35; p < 0.001). The multicultural environment significantly moderates this relationship (β = 0.18; p < 0.01). Simple slope analysis indicated that in dormitories with high-quality multicultural management, the relationship between emotional intelligence and social skills is strong and positive (β = 0.48; p < 0.001). Conversely, in poorly managed multicultural environments, this relationship becomes non-significant (β = 0.10; p > 0.05). These findings confirm that the translation of internal emotional capacity into external social competence is contingent on the dormitory's social climate. The study contributes to educational psychology by validating a moderation model in Indonesian pesantren.